Whole brain functional recordings at cellular resolution in zebrafish larvae with 3D scanning multiphoton microscopy - Matteo Bruzzone (Nature Portfolio, 2021)
Abstract Optical recordings of neuronal activity at cellular resolution represent an invaluable tool to investigate brain mechanisms. Zebrafish larvae is one of the few model organisms where, using fluorescence-based reporters of the cell activity, it is possible to optically reconstruct the neuronal dynamics across the whole brain. Typically, leveraging the reduced light scattering, methods like lightsheet, structured illumination, and light-field microscopy use spatially extended excitation profiles to detect in parallel activity signals from multiple cells. Here, we present an alternative design for whole brain imaging based on sequential 3D point-scanning excitation. Our approach relies on a multiphoton microscope integrating an electrically tunable lens. We first apply our approach, adopting the GCaMP6s activity reporter, to detect functional responses from retinal ganglion cells (RGC) arborization fields at different depths within the zebrafish larva midbrain. Then, in larvae expressing a nuclear localized GCaMP6s, we recorded whole brain activity with cellular resolution. Adopting a semi-automatic cell segmentation, this allowed reconstructing the activity from up to 52,000 individual neurons across the brain. In conclusion, this design can easily retrofit existing imaging systems and represents a compact, versatile and reliable tool to investigate neuronal activity across the larva brain at high resolution.